MENGIMPLEMENTASIKAN MODEL JEMBATAN KELEDAI UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA - Heni Purwitri (Balai Diklat Keagamaan Bandung, 2023)
This study aims to determine the increase in and learning outcomes after the implementation of learning model Donkey Bridge dan Contextual Teaching and Learning. This research is classroom action research (PTK) is conducted in two cycles. The subjects were students of class V MIN 1 Kota Tasikmalaya totaling 20 pupils. Collecting data using observation method for learning activities and methods of testing for learning outcomes. Data were analyzed to determine the mean percentage. The results showed that an increase in the percentage of learning activities and learning outcomes. At the first cycle average percentage of students learning outcomes in action I amounted to 70,95 (low category) and action II amounted to 75,95 (middle category) with learning activities amounted to 50% (low category). At the second cycle the average percentage of students learning outcomes amounted to 87,90 (high category) and action II amounted to 92,75 (high category) with learning activities amounted to 90% (high category). The implementation of Donkey Bridge dan Contextual Teaching and Learning prove to increase the level of learning outcomes significantly and be able to improve students’s activities.